Darkness Visible: A Consideration of Alternative Directions and Outcomes of Transformative Learning Theory, Teaching and Practice - Dana Naughton; Fred M. Schied (Adult Education Research Conference, 2012)
Transformative learning theory has enjoyed a thirty-plus year history as a dominant adult learning theory. It has been the subject of innumerable articles and books as well as meriting its own journal, conference and graduate degrees. Yet, the fertile nature of this theory to produce such a wide swath of scholarship is deceiving and, indeed, surprisingly limited in its reach. The major goal of this symposium is to challenge current discourse of transformative learning theory, teaching and practice which seems almost wholly tethered to scholarship on outcomes that result in individual healing or attainment of more enlightened states; or collective actions with goals firmly embedded in the promulgation of social justice.